Effects of a specific trunk and shoulder strength training program on throwing velocity and accuracy: a study among Hungarian first-league female handball players - Sinka, G. C.; Mayer, Á.; Tállay, A.; Tátrai, M.; Tábori, L.; Papp, E.; Pavlik, A. (Sports, 2024)
The aim of the study was to record shoulder and trunk stability of elite female handball players and to investigate their effect on throwing velocity and accuracy. 151 female handball players (9 teams in total) from the Hungarian first league participated in a mid-season conditional survey. The study included tests of trunk and shoulder stability, and measurements of factors affecting shoulder stability, as well as throwing speed and throwing accuracy. After the conditional survey, 18 players were selected for the intervention group (IG) and 18 players for the control group (CG). Significant relationships were found between the medial stability of the shoulder joint (Y-balance) and throwing accuracy (upper right corner) (r = 0.766; p < 0.001), throwing accuracy (upper left corner) (r = 0.729; p < 0.001), total throwing accuracy (r = 0.907; p < 0.001). The IG showed significant improvement in trunk stability (p < 0.001), shoulder joint stability (p < 0.001), throwing velocity (p < 0.001), and throwing accuracy (p = 0.002), compared to the CG. These findings support the idea that trunk and shoulder stability are related to throwing performance of female handball players. Measuring and training these aforementioned factors, particularly medial shoulder stability, may be a valuable adjunct to improving throwing accuracy and throwing velocity.